Investigation of the Temperature Distribution of a Small Solar - Evin, Duygu; Uçar, Aynur (My University, 2019)
Environmental friendly and sustainable energy policies are gaining importance day by day. A prototype solar chimney constructed inElazig is investigated experimentally in terms of temperature distribution and solar chimney efficiency. Elazig is in the third degreeday region where the temperature varies between -15 ° C and + 42 ° C. The experimental results showed that the efficiency depends onheight of the chimney and the temperature of ambient. The higher the height of the chimney, the more is the efficiency. However, theeffect of ambient temperature on the efficiency seems to be very low. It was seen that, solar chimney system can be an alternative systemfor energy production under Elazig conditions.
Keywords: Fizik; Uygulamalı